Absorptive capacity, economic freedom and the conditional effects of regional policy - Jonathan Eberle; Thomas Brenner; Timo Mitze (Philipps-University Marburg, Department of Geography, 2018)
This paper analyzes the role played by regional conditioning factors, namely absorptive capacity and economic freedom, for the working of regional policy in Germany. We construct synthetic composite indicators to measure differences in these factors across German regions and stratify regions by their respective values. We then identify the subsample-specific transmission channels of regional policies in a spatial panel vector-autoregressive (VAR) framework and compare the direction and magnitude of effects by impulse-response function analysis and ex-post ttests. The results point to two main channels of policy impact: While regions with low levels of absorptive capacity and economic freedom benefit from public funding only in terms of a traditional funding channel (i.e. higher investment rates and partly increased human capital levels), the link between regional policy, GDP and technology growth is very weak for these regions. In comparison, our findings hint at significant positive effects on regional GDP per workforce and patent activity for regions with a high absorptive capacity and economic freedom (i.e. a knowledgebased funding channel). This underlines the role of regional conditions for the direction and magnitude of funding effects and should be considered by policy makers as a means to trigger policy effectiveness in times of stagnating or decreasing funding volumes.
Keywords: C33; R11; R58; O38; O47; 330; regional policy; production function; absorptive capacity; economic freedom; SpPVAR; impulse-response functions